Can one laptop per child save the world's poor? - Warschauer, Mark; Ames, Morgan (Journal of International Affairs)
The One Laptop per Child (OLPC) program is one of the most ambitious educational reform initiatives the world has ever seen. The program has developed a radically new low-cost laptop computer and aggressively promoted its plans to put the computer in the hands of hundreds of millions of children around the world, including in the most impoverished nations. Though fewer than 2 million of OLPC's XO computers have been distributed as of this writing, the initiative has caught the attention of world leaders, influenced developments in the global computer industry and sparked controversy and debate about the best way to improve the lot of the world's poor. With six years having passed since Nicholas Negroponte first unveiled the idea, this paper appraises the program's progress and impact and, in so doing, takes afresh look at OLPC's assumptions. The paper reviews the theoretical underpinnings of OLPC, analyzes the program's development and summarizes the current state of OLPC deployments around the world. The analysis reveals that provision of individual laptops is a Utopian vision for the children in the poorest countries, whose educational and social futures could be more effectively improved if the same investments were instead made on more sustainable and proven interventions. Middle-and high-income countries may have a stronger rationale for providing individual laptops to children, but will still want to eschew OLPC's technocentric vision. In summary, OLPC represents the latest in a long line of technologically Utopian development schemes that have unsuccessfully attempted to solve complex social problems with overly simplistic solutions. Reprinted by permission of the publisher.